Finite element simulation of shear and compact tension tests on timber - Eliška Šmídová; Petr Kabele (Acta Polytechnica CTU Proceedings)
The non-linear finite element simulation of the ASTM shear and pre-stressed compact tension tests was conducted. Tested specimens were cut from the glued laminated timber made of European spruce (Picea abies) with the lamina thickness of 10.5 mm and 45 mm. The 2D homogeneous orthotropic constitutive model of the tensile-shear fracture in timber, which has been proposed by the authors, was used. The model calibration was adopted from the authors’ recent experimental study. The numerical results show that the model can adequately reproduce both the experimental response and the crack pattern, which in certain cases comprises of cracking parallel or perpendicular to fibers. Furthermore, the results confirm that the value of the parameter fASTMxy , obtained from ASTM shear test as the maximum attained force divided by the shearing area, represents the averaged stress at the failure plane, while the extreme stress experienced by the material is much higher.